TRANSFORMASI SARANA DAN PRASARANA MADRASAH MELALUI TOTAL QUALITY MANAGEMENT: STUDI KASUS MTS AL KAUTSAR TENGGARONG - Muhammad Nasir; Ahmad Ridani; Muhammad Aulia Rahman; Siti Hardyanti (STKIP Subang, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in managing facilities and infrastructure at MTs Al Kautsar Tenggarong. The background of this research stems from the initial condition of the madrasah, which was located on Jl. Danau Aji with limited land, resulting in the absence of a schoolyard and the inability to conduct flag ceremonies. Through the dedication of the former principal, the late Drs. H. Fahruddin, the madrasah was able to purchase new land, build a schoolyard, and provide dormitories for students coming from distant villages. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the Miles & Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the modernization of facilities and infrastructure has significantly impacted teaching and learning activities, character development, and inclusive access to education. An interview with the current principal, Mrs. Miftahul Jannah, S.Pd., emphasized that TQM-based management of facilities must be continuously evaluated and improved to meet contemporary demands. Stakeholder support also plays a crucial role in sustaining quality improvement. Therefore, the application of TQM has proven effective in enhancing the quality of Islamic education in alignment with societal needs.